Partial root-zone drying subsurface drip irrigation increased the alfalfa quality yield but decreased the alfalfa quality content - Wang, Yadong; Xu, Chong; Gu, Qian; Shi, Yalong; Chen, Jiale; Wu, Honghui; He, Jing; Li, Xingfu; Han, Liliang; Su, Derong (Frontiers in Plant Science, 2024)
Water shortage seriously restricts the development of grassland agriculture in arid land and dramatically impacts alfalfa (Medicago sativa L.) quality content and hay yield. Reasonable irrigation methods have the potential to enhance the alfalfa quality content, hay yield, and thus quality yield. Whether partial root-zone drying subsurface drip irrigation (PRDSDI) improves the alfalfa quality yield, quality content, and hay yield is still unknown compared with conventional subsurface drip irrigation (CSDI). The effects of PRDSDI compared with that of CSDI and the interaction with irrigation volume (10 mm/week, 20 mm/week, and 30 mm/week) on the alfalfa quality yield were investigated in 2017–2018 and explained the change in quality yield with the alfalfa quality content and hay yield. Here, the results showed that PRDSDI did not increase the alfalfa quality yield in 2 years. PRDSDI significantly increased acid detergent fiber by 13.3% and 12.2% in 2018 with 10-mm and 20-mm irrigation volumes and neutral detergent fiber by 16.2%, 13.2%, and 12.6% in 2017 with 10-mm, 20-mm, and 30-mm irrigation volumes, respectively. PRDSDI significantly decreased the crude protein by 5.4% and 8.4% in 2018 with 10-mm and 20-mm irrigation volumes and relative feed value by 15.0% with 20-mm irrigation volume in 2017 and 9.8% with 10-mm irrigation volume in 2018, respectively. In addition, PRDSDI significantly increased the alfalfa average hay yield by 49.5% and 59.6% with 10-mm and 20-mm irrigation volumes in 2018, respectively. Our results provide a counterexample for PRDSDI to improve crop quality. Although there was no significant improvement in average quality yield by PRDSDI, the positive impact of average hay yield on quality yield outweighed the negative impact of quality content. Thus, it has the potential to improve quality yields. The novel findings regarding the effects of PRDSDI on quality yield are potentially favorable for the forage feed value in water-limited areas.